Physicochemical Characterization Patin Fish Oil (Pangasius micronema) Is Refined Using Bentonite and Activated Carbon. - Indah Indah; Abdul Rohman; Lily Arsanti Lestari (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2022)
Abstract: This study aims to determine the physical and chemical quality of fish oil from the flesh of Pangasius microcinema. The quality of extracted fish oil can be improved through a refining process. Before and after the purification process, the quality of crude fish oil was analyzed, including acid value (AV), saponification value (SV), iodine value (IV), peroxide value (PV), and p-anisidine value (An-V). The results of the characterization of patin fish oil (PFO) in meat were carried out with 3 purifications, namely purification without activated carbon purification treatment with bentonite, the value of susceptibility to acid value, peroxide value, saponification value, iodine value, and p-anisidinee value, which ranged from 1.92-2.64 mg KOH/g, peroxide value 3.76-4.87 meq O2/kg, iodine value 80.46-81.39 g I2/100g, saponification value 189.48-196.75 mg KOH/g, and p-anisidinee value 5.95-8.93 meq/kg. The best refining process is the oil extracted from patin fish oil meat oil and distilled using bentonite from dry rendering because the processed fish oil is good in the standards set by the International Association of Fish Flour Producers, Indonesian Fish Oil Standards, and as food fish oil grades.